Antara Tanggung Jawab dan Kelelahan: Eksplorasi Strategi Adaptif Perawat dalam Menghadapi Beban kerja: Penelitian - Iswadi; Durrotul Baidho (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Nurses play a crucial role in healthcare services but frequently face a high workload, including physical and mental demands, limited resources, patient dependency, and an imbalanced nurse-to-patient ratio. These conditions contribute to increased stress and decreased performance among clinical nurses, particularly in inpatient care settings. This study aims to explore the perceptions of clinical nurses regarding high workloads in the inpatient unit of Sungai Bahar Regional Public Hospital. A qualitative method with a descriptive phenomenological approach was employed. Nine participants were selected through purposive sampling. Data were collected via in-depth interviews and analyzed using Collaizi's method. Four main themes emerged from the data: (1) general overview of high workload with unfulfilled welfare and recognition; (2) contributing factors to workload, especially the disproportionate number of patients to nurses; (3) the impact of workload on emotional control and patient safety; and (4) nurses' coping strategies and expectations, including task delegation, prioritization, time management, and self-distraction to reduce stress. These findings provide in-depth insights into nurses' experiences and may inform hospital management policies aimed at improving nurse well-being and patient care quality..